Determination of Calcium Levels with XRF and Literature Review of its Bioavailability in Vitro of Dahlia Tubers Syrop (Dahlia Pinnata Cav.) (Indonesian Journal of Chemical Science, 2022)
Calcium bioavailability (Ca) states the ratio of available calcium to the amount of calcium consumed during metabolic processes. The bioavailability of Ca is calculated by the difference between the amount of Ca in the consumed food product and the excreted feces. In this research, calcium can be obtained from dahlia tuber syrup (Dahlia pinnata Cav.). The purpose of this study was to discuss the determination of Ca levels and a literature review of the Ca bioavailability of dahlia tuber syrup (Dahlia pinnata Cav.) in vitro. The content of Ca in dahlia tubers was determined experimentally using an XRF (X-Ray Fluorescence) instrument. The bioavailability of Ca was determined by predicting the ratio of inulin and Ca content. The results showed that the Ca content of dahlia tuber syrup was 197,57 ppm. The bioavailability of Ca in dahlia tuber syrup in vitro was predicted from a relatively high ratio of inulin content of around 65-86% and FOS levels from hydrolysis of 5% dahlia tuber inulin about 15,41-29,38% or an average of 22,395%, on Ca levels is 81,46-85,33%. The results of the study on the bioavailability of Ca in dahlia tuber syrup (Dahlia pinnata Cav.) have a fairly high level. The high bioavailability of Ca can increase calcium absorption in the body and have health effects, among others, for heart and bone health.